Sights of London the Diorama : Ruins in a fog. - Daguerre, Louis Jacques Mandé, 1787-1851 (Victorian popular culture. Moving pictures, optical entertainments and the advent of cinema., 2012)
Article describes the engraving by Daguerre, and another by Bouton, View of St. Cloud and environs of Paris, as exhibited at Daguerre's London Diorama in Regent's Park.